2004
DOI: 10.1097/01.ju.0000091106.61065.e3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Deformation Induced Apoptosis in Human Proximal Renal Tubular Epithelial Cells is Caspase Dependent

Abstract: Altering HSP-70 expression and manipulating the caspase cell death proteases represent a novel pathway to protect against renal tubular cell apoptosis and the potential for progression to renal failure in UO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 14 publications
6
34
0
Order By: Relevance
“…Accordingly, previous studies have shown that neither oxidative and nor osmotic stress induces HSP27 and HSP70 expression in mesangial cells (8,21). Lack of response to these insults appears to be specific to glomerular cells as stretch has been shown to induce HSP70 overexpression in other cell types such as tubular epithelial cells (26) and vascular smooth muscle cells (36). Furthermore, our observation that both HSP27 and HSP70 are strongly induced by exposure to thermal stress indicates that the inability to mount an effective stress response is limited to diabetes-related insults.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous studies have shown that neither oxidative and nor osmotic stress induces HSP27 and HSP70 expression in mesangial cells (8,21). Lack of response to these insults appears to be specific to glomerular cells as stretch has been shown to induce HSP70 overexpression in other cell types such as tubular epithelial cells (26) and vascular smooth muscle cells (36). Furthermore, our observation that both HSP27 and HSP70 are strongly induced by exposure to thermal stress indicates that the inability to mount an effective stress response is limited to diabetes-related insults.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal pressure can also be dramatically elevated in kidney disease states [11]. Indeed, obstructive uropathy is associated with a major increase in intratubular pressure, in excess of 60 mm Hg, leading to tubular circumferential stretch [16][17][18][19][20]. Stretching as well as compression of renal epithelial cells also occur in polycystic kidney disease (PKD) patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the pathways of programmed cell death can be activated by mechanical stretch, alone. Caspase 3-mediated apoptosis is induced by applying gentle stretch to the substratum on which monolayers of human kidney cells are cultured (20). Similarly, mechanical strain was shown to activate BAD dephosphorylation in cultured proximal tubular cells (15).…”
mentioning
confidence: 99%